A selective study of clinical diphteric myocarditis - A. Samik Wahab; Pustika Sastroamidjojo (Indonesian Pediatric Society, 1973)
Diphtheria is still not a rare disease in Indonesia, especially not in crowded areas (Kwari et aI., 1965; Maemunah et aI., 1965; Asril et aI., 1968), often with high mortality in hospitals (Kwari et aI., 1965; Maemunah et aI., 1965; Asril et aI., 1968; Sulianti, 1971).